(3EUMGMGJ EfLjd eJis - (3GdbOjS eJjs
(3ChdgG (B:s
(3bGHd GdJhHI hZGaQ GdPfH Edi Gddg fHJgd hYdjg ai SGFQ GdCehQ fYJeO s
(3BNQgG (B:s
(3hcGf Pdc fMh GdSGOSI CNHQg Ydi fMh GdhUjI s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdOjGfGJ GdCNQis